Uptake and correlates of cervical cancer screening among HIV-infected women attending HIV care in Uganda - Rhoda K. Wanyenze; John Baptist Bwanika; Jolly Beyeza-Kashesya; Shaban Mugerwa; Jim Arinaitwe; Joseph K. B. Matovu; Violet Gwokyalya; Dickson Kasozi; Justine Bukenya; Fred Makumbi (Taylor & Francis Group, 2017)
Background: Human immunodeficiency virus (HIV)-infected women are at high risk of cervical cancer. Objective: This study assessed uptake and correlates of cervical screening among HIV-infected women in care in Uganda. Methods: A nationally representative cross-sectional survey of HIV-infected women in care was conducted from August to November 2016. Structured interviews were conducted with 5198 women aged 15-49 years, from 245 HIV clinics. Knowledge and uptake of cervical screening and human papillomavirus (HPV) vaccination were determined. Correlates of cervical screening were assessed with modified Poisson regression to obtain prevalence ratios (PRs) using Stata version 12.0. Results: Overall, 94.0% (n = 4858) had ever heard of cervical screening and 66% (n = 3732) knew a screening site. However, 47.4% (n = 2302) did not know the schedule for screening and 50% (n = 2409) did not know the symptoms of cervical cancer. One-third (33.7%; n = 1719) rated their risk of cervical cancer as low. Uptake of screening was 30.3% (n = 1561). Women who had never been screened cited lack of information (29.6%; n = 1059) and no time (25.5%; n = 913) as the main reasons. Increased likelihood of screening was associated with receipt of HIV care at a level II health center [adj. PR 1.89, 95% confidence interval (CI) 1.29-2.76] and private facilities (adj. PR 1.68, 95% CI 1.16-3.21), knowledge of cervical screening (adj. PR 2.19, 95% CI 1.78-2.70), where to go for screening (adj. PR 6.47, 95% CI 3.69-11.36), and low perception of risk (adj. PR 1.52, 95% CI 1.14-2.03). HPV vaccination was 2%. Conclusions: Cervical screening and HPV vaccination uptake were very low among HIV-infected women in care in Uganda. Improved knowledge of cervical screening schedules and sites, and addressing fears and risk perception may increase uptake of cervical screening in this vulnerable population.